Design of low noise amplifier using feedback and balanced technique for WLAN application - Mohamad Harris, Misran; Maizatul Alice, Meor Said; Mohd Azlishah, Othman; Mohd Muzafar, Ismail; Hamzah Asyrani, Sulaiman; K.G., Cheng (Malaysian Technical Universities Network (MTUN), 2013)
Malaysian Technical Universities Conference on Engineering and Technology (MUCET) 2012 organised by technical universities under the Malaysian Technical Universities Network (MTUN), 20th - 21st November 2012 at Hotel Seri Malaysia, Kangar, Perlis.